Correlates of Common Mental Disorders Among Dutch Women Who Have Had an Abortion: A Longitudinal Cohort Study. Issue 2 (28th April 2017) - van Ditzhuijzen, Jenneke; ten Have, Margreet; de Graaf, Ron; van Nijnatten, Carolus H.C.J.; Vollebergh, Wilma A.M.
Abstract : CONTEXT: Credible research has not found any evidence that abortion causes mental disorders. It is not known, however, whether abortion‐specific risk indicators and other variables are associated with the incidence or recurrence of mental disorders after abortion. METHODS: As part of a prospective cohort study conducted in the Netherlands, 325 women were interviewed between April 2010 and January 2011, between 20 and 40 days after having an abortion; 264 were followed up an average of 2.7 years later. Associations between selected baseline variables and postabortion incident or recurrent mental disorders among the 199 women at risk were investigated using bivariate and multivariate logistic regression analyses. RESULTS: Thirty‐two percent of women at risk of an incident or recurrent mental disorder experienced one after the abortion. In multivariate analyses, no abortion‐related variables (e.g., history of multiple abortions, second‐trimester abortion, preabortion decision difficulty or uncertainty, and postabortion negative emotions) were associated with experience of any postabortion incident or recurrent mental disorders. The outcome was positively associated with having conceived within an unstable relationship (odds ratio, 3.0), number of negative life events in the past year (1.4) and having a history of mental disorders (2.4). CONCLUSIONS: Correlates of postabortion mental disorders were variables that have been identified as general risk factors for mental disorders, which supports the idea that abortion does not pose specific risks to future mental health. Future research should investigate in what way unstable relationships, adverse life events and psychiatric history affect postabortion mental health.